PENINGKATAN KETERAMPILAN IBU RUMAH TANGGA MELALUI PEMBUATAN OLAHAN IKAN SEBAGAI UPAYA PENCEGAHAN STUNTING - Rahmawati; Akbardiansyah; Rosi Rahayu; Muhammad Arif; Sri Ayu Insani; Afdhal Fuadi; Hamidi; Muhammad Agam Thahir; Rudi Hermi (LPPM Universitas Al Muslim, 2023)
The nutritional content of fish is very high in protein and omega 3 fatty acids, but there is still little interest in eating fish among children. The government is trying to prevent stunting by launching the GEMARIKAN (Gemar Makan Ikan/Fond of eating fish) program to fulfill nutrition sourced from fish. Fish are generally less popular because their shape makes them uninteresting and boring, so interest in eating fish decreases. Housewives are encouraged to play a role in fulfilling children's nutrition through fish intake using various techniques, one of which is processing fish into a variety fish-based food. Alternative fish-based food is made to attract families to consume it by empowering groups of housewives and young women. This training aimed to educate about alternative fish-based food and recommend business opportunities to support additional family income. Training activities were carried out through mentoring and counseling for 20 housewives and young women from Gampong Blang Padang, by forming small groups and providing education regarding techniques for processing fish into dimsum products, fish sticks and fish nuggets. The results of the training showed that housewives and young women were able to make more varied fish preparations. Apart from that, participants received counseling about the benefits of fish for health, not only as an ingredient in making various types of processed fish food that have nutritional and economic value.